Analysis and Relevance of Surah Al-Mulk Verse 15 in Daily Life - Rio Arjaya; Dwi Noviani; Muhammad Iqbal Latansa; Fahrul Gunadi (Program Pascasarjana UIN Sumatera Utara, 2024)
Surah Al-Mulk, one of the chapters in the Qur'an, holds an important position in Islamic teachings. Its verses not only emphasize the beauty of language and literature but also contain profound meanings related to human life and the creation of the universe. One particularly noteworthy verse is verse 15, which offers valuable guidance and lessons for humanity.Verse 15 of Surah Al-Mulk (Surah 67) holds significant importance in the Qur'an, especially in the context of the overarching themes presented in this chapter. Surah Al-Mulk generally discusses Allah's power, the creation of the heavens and the earth, and humanity's responsibility as stewards on Earth.This research employs a qualitative method with a library research approach. The qualitative approach focuses on understanding and interpreting social phenomena from the participants' perspectives. The meaning and wisdom of Surah Al-Mulk, verse 15, highlight several important points regarding the relationship between humans and their Creator, as well as their responsibilities as beings on Earth. This verse reminds us of the importance of spiritual awareness, encouraging individuals to reflect on Allah's creation as a sign of His greatness. By understanding and appreciating our surroundings, we can draw closer to Allah and experience His presence in our daily lives.